Preparation and optical properties of ZnSe films - E.M. Sofronova; D.S. Sofronov; V.V. Starikov; D.I. Kurbatov; А.S. Оpanasyuk; P.V. Маtеychеnkо (Журнал нано- та електронної фізики)
Microwave method was used for the synthesis and purification of the initial zinc selenide salt. The obtaining powder was used for deposition of the ZnSe thin films on the ultrasonically cleaned glass substrates using the quasi-closed space evaporation under the following conditions: the constant evaporation temperature Te = 800 °C, the temperature of the substrate Ts = 100-600 °C. The investigation of optical characteristics allow to calculate the band gap of condensates and specify their phase composition.